MODEL PENGEMBANGAN PENINGKATAN KINERJA SDM PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA KENDARI - Try Reno Saputri (Jurnal Riset Bisnis Indonesia, 2014)
This study aims to development a model of human resources performance improvement in populationand civil registration offices of Kendari. In this regard, research tried to examine how the variables ofknowledge, skills, attitudes, and human resources abillity affect the human resoures of performanceimprovement at the Department of Population and Civil Registration Kendari. This study used 52sample which calected by sensus method, and PLS has been used to analysis. The results of thestudy show that : (1) knowledge has a positive effect on human resources abillity, (2) skills has apositive effect on the human resources of abillity, (3) attitude has a positive influence on the humanresources of ability, (4) knowledge is not a influence on the human resources of performance, (5)skills has a positive effect on the human resources of performance, (6) attitude has a positive effecton the human resources of performance, and (7) the ability of human resources has a positive effecton the human resources of performance.Keywords: Knowledge, Skills, Attitude, Human Resources of Abillity, dan Human Resources ofPerformance.